2011
DOI: 10.1111/j.1365-2559.2011.03884.x
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde dehydrogenase 1 expression predicts poor prognosis in triple-negative breast cancer

Abstract: ALDH1 expression in carcinoma cells is an independent prognostic factor in TN breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
53
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 6 publications
(14 reference statements)
6
53
1
Order By: Relevance
“…In contrast, we found that ALDH1 expression was associated with Her2/neu overexpression. With similar results currently emerging from groups in Japan, we propose that ALDH1 expression is associated with Her2/neu-overexpressing breast cancers in Asian patients [11,14].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In contrast, we found that ALDH1 expression was associated with Her2/neu overexpression. With similar results currently emerging from groups in Japan, we propose that ALDH1 expression is associated with Her2/neu-overexpressing breast cancers in Asian patients [11,14].…”
Section: Discussionsupporting
confidence: 59%
“…Some studies have reported the association of ALDH1 expression with poor prognosis and factors associated with aggressive disease such as estrogen receptor (ER) negativity and the expression of basal-like markers [11,12]. ALDH1 positivity has also been shown to be correlated with poor prognosis, especially in lymph node-positive cancers, triple-negative cancers, and inflammatory breast cancers [13][14][15]. Furthermore, ALDH1 expression has been shown to be associated with resistance to chemotherapy [16,17].…”
mentioning
confidence: 99%
“…Several investigators have demonstrated its clinical significance as a prognostic indicator of breast cancer, and may become a promising target for cancer therapy. ALDH1 expression in carcinoma cells is an independent prognostic factor in TNBC patients (Ohi et al, 2011). In addition, Li et al study support the concept that the expression of ALDH1 is higher in TNBC than in non-TNBC, which may be clinically meaningful for a better understanding of the poor prognosis of TNBC patients .…”
Section: Biomarkers For Targeted Therapysupporting
confidence: 60%
“…In this study, we investigated two cancer stem-like cell/tumor-initiating cell markers. Aldehyde dehydrogenase 1(ALDH1) is a cytosolic isoform of ALDH, and high levels of its activity are seen not only in hematopoietic stem/ progenitor cells but also in solid cancers (eg, breast, 16,17 colorectal, 18 pancreas, 19 bladder 20 and prostate 21 cancers). Furthermore, expression of ALDH1 is a predictor of poor clinical outcome in the breast, 16,22 lung, 23 pancreatic 19 and bladder 20 cancers.…”
mentioning
confidence: 99%